Implementasi Sistem Infomasi Desa Berdasarkan Undang-Undang No 6 Tahun 2014 Tentang Desa pada Kantor Desa Pematang Gajah Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Magna Devenia Br Manalu; Mohammad Ihsan; Ovie Yanti (Ebisnis Manajemen, 2025)
This study aims to analyze the implementation of the Village Information System (SID) in Pematang Gajah Village based on Article 86 of Law No. 6 of 2014 concerning Villages, as well as identify inhibiting and supporting factors in its implementation. Pematang Gajah Village has been developing the Village Website since 2022 as a form of SID implementation. This research uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results show that even though SID has been equipped with hardware, software, and networks, access to information to the public has not been optimal due to uneven socialization. In addition, SID does not contain data on the development of villages and rural areas, and has not been supported by planning information from local governments. The main inhibiting factors include limited understanding of the community and village apparatus towards technology, incomplete socialization, and unstable internet networks. On the other hand, the existence of village websites, budget allocation, and the availability of technological devices are significant supporting factors. The commitment of village officials in gradually increasing the use of SID is also an important capital in system sustainability. This study recommends increasing human resource capacity, equitable distribution of socialization, and strengthening infrastructure support as strategic steps in optimizing SID at the village level.